Tomato FK506 Binding Protein 12KD (FKBP12) Mediates the Interaction between Rapamycin and Target of Rapamycin (TOR) - Xiong, Fangjie; Dong, Pan; Liu, Mei; Xie, Gengxin; Wang, Kai; Zhuo, Fengping; Feng, Li; Yang, Lu; Li, Zhengguo; Ren, Maozhi (Frontiers in Plant Science, 2016)
Target of Rapamycin (TOR) signaling is an important regulator in multiple organisms including yeast, plants and animals. However, the TOR signaling in plants is much less understood as compared to that in yeast and animals. TOR kinase can be efficiently suppressed by rapamycin in the presence of functional FK506 Binding Protein 12KD (FKBP12) in yeast and animals. In most examined higher plants rapamycin fails to inhibit TOR kinase due to the non-functional FKBP12. Here we find that tomato plants showed obvious growth inhibition when treated with rapamycin and the inhibitory phenotype is similar to suppression of TOR causing by active-site TOR inhibitors (asTORis) such as KU63794, AZD8055 and Torin1. The chemical genetic assays using TOR inhibitors and heterologous expressing SlFKBP12 in Arabidopsis indicated that the TOR signaling is functional in tomato. The protein gel shifting and TOR inhibitors combination assays showed that SlFKBP12 can mediate the interaction between rapamycin and TOR. Furthermore, comparative expression profiling analysis between treatments with rapamycin and KU63794 identified highly overlapped Differentially Expressed Genes (DEGs) which are involved in many anabolic and catabolic processes, such as photosynthesis, cell wall restructuring, and senescence in tomato. These observations suggest that SlFFBP12 is functional in tomato. The results provided basic information of TOR signaling in tomato, and also some new insights into how TOR controls plant growth and development through reprogramming the transcription profiles